The Influence of Work Discipline and Organizational Communication on the Performance of Phylon Section Employees at PT Adis Dimension Footwear Tangerang Regency - Nurputradi, Nanda; Sukarya, Yaya; Setiawan, Temmy (IJOSPOL - International Journal of Social, Policy and Law, 2026)
This study aims to determine the simultaneous influence of work discipline and organizational communication on the performance of employees in the Phylon Injection department at PT. Adis Dimension Footwear, Balaraja, Tangerang.This study employed a quantitative descriptive method, which describes variables as they are, supported by numerical data derived from actual conditions. The population in this study was all employees in the Phylon Injection department at PT. Adis Dimension Footwear, Balaraja, Tangerang. The sample size was 71 respondents. The sampling technique used was simple random sampling. The Slovin formula was used to determine a representative sample size in quantitative research. Data analysis used multiple linear regression analysis with SPSS 26.The results of this study indicate that (1) partially, work discipline significantly influences the performance of employees in the Phylon Injection department at PT. Adis Dimension Footwear, Balaraja, Tangerang, as indicated by the calculated t-value > t-table (2.033 > 1.995), and a significance value of 0.000, which is less than the 0.05 threshold. Thus, Ha is accepted and H0 is rejected. (2) Partially, organizational communication significantly influences the performance of employees in the Phylon Injection section at PT. Adis Dimension Footwear Balaraja-Tangerang, as indicated by the calculated t value> t table (5.233>1.995) and a significance value of 0.000 smaller than the significance value of 0.05. Thus, Ha is accepted and H0 is rejected. (3) Simultaneously, work discipline and organizational communication significantly influence the performance of employees in the Phylon Injection section at PT. Adis Dimension Footwear Balaraja-Tangerang, as indicated by the calculated F> F table (20.609>3.13) with a significance level of 0.000. Thus, Ha is accepted and H0 is rejected.Based on the results of the study, it can be concluded that the variables of work discipline and organizational communication, both partially and simultaneously, have a significant influence on the performance of employees in the Phylon Injection section at PT. Adis Dimension Footwear Balaraja-Tangerang.